Criminology of Serial Poisoners - Farrell, Michael (Springer International Publishing, 2018)
This book examines serial homicidal poisonings in the modern era, to improve our contemporary understanding of poisons, poisoners, and investigation. Drawing on cases of serial poisoning from around the world, the book defines key terms, examines theories and explanations of serial homicide in relation to serial poisoning, explores the features of the poisons and examines the demographic characteristics of perpetrators of serial poisoning and their victims. It considers healthcare serial poisoning as a specific issue. Overall, it provides an outline for developing a criminology of serial poisoning homicide.